Kisspeptin-10 Enhanced Egg Production in Quails Associated with the Increase of Triglyceride Synthesis in Liver - Wu, J. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
Our previous results showed that kisspeptin-10 (Kp-10) injections via intraperitoneal (i.p.) once daily for three weeks notably promoted the egg laying rate in quails. In order to investigate the mechanism behind the effects of Kp-10 on enhancing the egg laying rate in birds, this study focused on the alternations of lipids synthesis in liver after Kp-10 injections. 75 female quails (22 d of age) were allocated to three groups randomly, and subjected to 0 (control, Con), 10 nmol (low dosage, L) and 100 nmol (high dosage, H) Kp-10 injections via i.p. once daily for three weeks, respectively. At d 52, quails were sacrificed and sampled for further analyses. Serum E(2) concentration was increased by Kp-10 injections, and reached statistical significance in H group. Serum triglyceride (TG) concentrations were increased by 46.7% in L group and 36.8% in H group, respectively, but did not reach statistical significance, and TG contents in liver were significantly elevated by Kp-10 injections in a dose-dependent manner. Serum total cholesterol (Tch) concentrations significantly decreased in H group, while in H group the hepatic Tch content was markedly increased. The level of non-esterified fatty acid (NEFA), apolipoprotein A1 and B (apoA1 and apoB) were not altered by Kp-10 injections. The genes expression of sterol regulatory element binding protein-1 (SREBP-1), fatty acid synthetase (FAS), apolipoprotein VLDL-II (apoVLDL-II), cholesterol 7α-hydroxylase (CYP7A1) and vitellogenin II (VTG-II) were significantly up-regulated by high but not low dosage of Kp-10 injection compared to the control group. However, the expression of SREBP-2, acetyl-CoA carboxylase (ACCα), malic enzyme (ME), stearoyl-CoA (Δ9) desaturase 1 (SCD1), apolipoprotein A1 (apoA1), fatty acid binding protein 2 (FABP2), 3-hydroxyl-3-methyl glutaryl-coenzyme A reductases (HMGCR), estrogen receptor α, β (ERα and β) mRNA were not affected by Kp-10 treatment. In line with hepatic mRNA abundance, hepatic SREBP1 protein content was significantly higher in H group. Although the mRNA expression was not altered, the content of ERα protein in liver was also significantly increased in H group. However, SREBP-2 protein content in liver was not changed by Kp-10 treatment. In conclusion, exogenous Kp-10 consecutive injections during juvenile stage significantly advanced the tempo of egg laying in quails, which was associated with the significant elevation in hepatic lipids synthesis and transport.